EVALUASI PENGERJAAN ULANG (REWORK) PADA PROYEK KONSTRUKSI GEDUNG DI SEMARANG - Ardhan Herdianto; Ayunda Dewi Ratih Tanjungsari; Arif Hidayat; Jati Utomo Dwi Hatmoko (Jurnal Karya Teknik Sipil, 2015)
Reworks on construction projects caused by errors in planning, working procedure errors, lack of supervision makes the results of work are not in accordance with the initial design and the construction. They can result in some of loss, such as cost, time, quality of work, and a decreased motivation. This study intends to evaluate the rework on the building construction project in Semarang with the aim to identifying the causative factor of rework, to knowing the magnitude of the risk and the impact caused of rework, knowing the parties responsible for the occurrence of rework and to find a solution to minimize it. A method of gathering data is done by conducting preliminary interviews to 6 companies construction in Semarang and spread of the questionnaires to the 60 respondents, but the application answered as much as 41 questionnaires. The risk management framework was used to determine the impact of rework on the construction project in terms of time and costs with a scale of 1-5. The results showed that the most dominant factor causes rework is a managerial factors. The type of work that is often experienced on rework is finishing and complementary. the greatest impact of rework on finishing work and complementary, with the impact on the time at 3.65 and the impact on the cost at 3.21. Parties responsible if rework occurs as a whole according to the perspective of the respondents there was party contractor amounted to 79.16%. The solution to minimizes rework effectivelly is to improve communication, supervision in the field, improve teamwork between the parties.